Assistance and Optimization of Personal Financial Management for Santripreneur in Islamic Campus Environment - Muhammad Syahrul Hidayat; Ahmad Munir Hamid; Syuhada' (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Weak personal financial management among santripreneurs remains a significant barrier to the sustainable growth of their businesses, particularly within Islamic educational institutions. This study aims to evaluate the effectiveness of a structured mentoring program in enhancing personal financial literacy and management practices among santripreneurs in the Islamic campus environment of Lamongan Regency, Indonesia. Employing a Participatory Action Research (PAR) approach, the program was implemented through four integrated stages: initial needs assessment, action planning, intervention execution, and reflective evaluation. A total of 40 participants were involved over a three-month period. The intervention consisted of training modules on financial record-keeping, budgeting, and the application of Islamic financial instruments. The findings revealed that 85% of participants successfully implemented the separation of personal and business finances, while 24.43% experienced an increase in business turnover. Furthermore, the utilization of Islamic financial services increased from 30% to 65% of participants. The reflective evaluation phase indicated a significant behavioral shift toward financial discipline, especially in cash flow monitoring and capital allocation. This study contributes to the literature on Islamic entrepreneurship by demonstrating the practical impact of financial mentoring in faith-based business environments and highlights the potential for replication in other Islamic boarding school settings.